Alleviating the Physician Shortage by Increasing Medical Student and Resident Physician Capacity in the North Midwest (Iowa, Minnesota, North Dakota, South Dakota, Wisconsin) - Nicholas Leifeld; George Ongoro; Patrick Bright; Peter Nalin (Journal of Regional Medical Campuses)
The authors’ central goal was to design a plan for the anticipated physician deficit in the North Midwest region of the United States. We analyzed the Association of American Medical Colleges’ (AAMC) 2024 projections, which have forewarned of a significant shortage by 2036. This study addresses this challenge by proposing targeted plans to augment medical student and resident capacity in Iowa, Minnesota, North Dakota, South Dakota, and Wisconsin. The purpose was to develop plans for each state to ensure an adequate supply of physicians to meet the growing demands on the healthcare systems. The calculations identified the approximate balance between the growing healthcare needs of the North Midwest region and the capacity of the existing medical education and residency training programs. We suggested the incremental expansion of medical student seats and residency positions over the next 10 years. We outlined how to bridge the physician gap while avoiding any undue stress on the existing systems.